Damage characteristics of ice projectile impacting on CF/BMI composite target at high speed. (September 2022) - Tang, Enling; Wang, Xinxin; Han, Yafei; Chang, Mengzhou; Chen, Chuang; Guo, Kai; He, Liping
Highlights: the finite element analysis software ABAQUS/Explicit was used to simulate the ice projectiles impacting on CF/BMI composite target. The influences of impact velocity, impact angle and ice projectiles size on the damage characteristics of CF/BMI composite target were studied by combining experiment with numerical simulation. the velocity threshold of macro scale failure of CF/BMI composite target is between 251m/s and 278m/s when the ice projectiles vertically impacts on the CF/BMI composite target; The delamination failure of CF/BMI composite target first occurs at the interface between braided layer and laminated structure, and the delamination failure area expands with the increase of ice projectile velocity. When the ice projectile obliquely impacts on the CF/BMI composite target, the stress and strain peaks of the CF/BMI composite target increase with the increase of the ice projectile velocity. Abstract: In order to simulate the dynamic mechanical response and damage characteristics of aircraft airframe materials under the impact load of hail, the Carbon Fiber/Bismaleimide (CF/BMI) composite materials used widely in aircraft airframes were taken as the research object in this paper. The finite element analysis software ABAQUS/Explicit was used to simulate the ice projectiles impacting on CF/BMI composite target. The influences of impact velocity, impact angle and ice projectiles size on the damage characteristics of CF/BMI composite target were studied by combining experiment with numerical simulation. The results show that the velocity threshold of macro-scale failure of the CF/BMI composite target is between 251m/s and 278m/s when the ice projectiles vertically impact on the CF/BMI composite target; The delamination failure of the CF/BMI composite target first occurs at the interface between braided layer and laminated structure, and the delamination failure area expands with the increase of ice projectile velocity. When the ice projectile velocity exceeds 278m/s, the damage area of the CF/BMI composite target increases linearly with the increase of ice projectile velocity. However, when the ice projectile obliquely impacts on the CF/BMI composite target, the stress and strain peaks of the CF/BMI composite target increase with the increase of the ice projectile velocity. For the same size ice projectile impacts on the CF/BMI composite target at the same speed, the damage caused by the impact angle of 60° is greater than that by the impact angle of 45°.